PREVALENCE ALONG WITH THE RISK FACTORS OF HYPERTENSION IN YOUNG ADULTS IN THE POPULATION UNDER STUDY: A CROSS-SECTIONAL STUDY - Bedarbakhat Khan; Noor Jehan Memon; Muhammad Amjad Kalhoro; Mamoona Shaikh; Mehwish; Durdana Inayat (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Hypertension (HTN) is the most prevalent cardiovascular disorder, and it is a vital risk factor for cardiovascular related mortality, contributing to 20–50% of all deaths. While extensive research has focused on HTN in older adults and the elderly, data on young adults are limited due to the perception that they are at a lesser risk for the development of the condition.Objectives: The aim of the present study is the determination the prevalence and associated risk of high blood pressure in individuals aged 20–40 years.Study design: A cross-sectional studyPlace and Duration: This study was conducted in Liaquat University of Medical & Health Sciences Jamshoro/Hyderabad from March 2023 to March 2024Methodology: This study was conducted to assess the prevalence of HTN and socio-demographic factors associated with it. Participants provided informed consent, and data collection was carried out using a systematic random sampling approach with semi-structured questionnaires that were predesigned and pretested. Blood pressure was recorded three times with a sphygmomanometer. The average value of all the readings was utilized for analysis. The data were analysed using SPSS version 26.Results: Out of the total 300 participants, 18% were diagnosed with HTN, and 51.7% were identified as pre-hypertensive. Key factors linked to HTN included age, type of family, marital status, family history, tobacco use, stress levels, and body mass index (BMI).Conclusion: This study highlights a high prevalence of HTN (18%) in the 20–40-year-old age group, indicating a potential increase in the cardiovascular disease burden within this population.